Journalism : A Very Short Introduction - Hargreaves, Ian (Oxford, New York Oxford University Press, 2014)
In this new edition of the Very Short Introduction to Journalism, Ian Hargreaves considers the role and place of journalism in our constantly evolving digital world. Exploring issues relating to privacy, democracy, the entertainment industry, and global social media, Hargreaves explores the shape and influence of journalism in years to come.
Include Index and Illustration
Keywords: Journalism -- Mass media -- Mass media--Social aspects